Magnetic resonance imaging of a solid, multilobular ameloblastoma in the mandible of a pony. (24th October 2012) - Koch, E.; Ryan, C.; Leitch, M.; Del Piero, F.; Boyle, A.
<x xml:space="preserve">Abstract</x> See also Clinical Commentary by Holmes